Pre-clerkship National Board of Medical Examiners Subject Examinations Versus End-of-Semester Final Examinations: How Well Do They Assess Preparedness for the United States Medical Licensing Examination Step 1? - Moreno, Marvi; Gonzalez, Pedro; Sieck, Blake; Simanton, Edward (Curēus (Palo Alto, CA), 2022)
BackgroundThe ability to provide performance insights of various United States Medical Licensing Examination (USMLE) Step 1 assessments is of great importance to medical educators. Two custom pre-clerkship assessments used at the Kirk Kerkorian School of Medicine at the University of Nevada, Las Vegas (KSOM) are National Board of Medical Examiners (NBME)-derived end-of-semester final examinations and subject examinations. The authors sought to determine if performance on these custom assessments can provide feedback on a medical student’s readiness to undertake the USMLE Step 1 examination.MethodologyDeidentified student performance data were provided by institutional databases for the KSOM graduating class of 2023 (N = 60). Pearson correlation analyses were utilized to evaluate the strength of the correlation between USMLE Step 1 performance and NBME subject examinations versus NBME end-of-semester final examinations.ResultsThe results indicated that the NBME end-of-semester final examinations have a statistically higher correlation to the USMLE Step 1 score than the majority of the individual NBME subject examinations. However, the mean NBME subject examination score (Semester 1: r = 0.53, p < 0.05; Semester 2: r = 0.58, p < 0.05) demonstrated significantly higher correlation to the USMLE Step 1 performance than the NBME end-of-semester final examination score for both Semesters 1 and 2 (Semester 1: r = 0.50, p < 0.05; Semester 2: r = 0.48, p < 0.05).ConclusionsThese results showed that the mean of the NBME subject examination score was a better metric to assess readiness for the USMLE Step 1 than the NBME end-of-semester final examinations. However, each NBME end-of-semester final examination score showed a better correlation than the majority of the NBME subject examinations.